The Effects of Daytime Psilocybin Administration on Sleep: Implications for Antidepressant Action - Dudysová, Daniela; Janků, Karolina; Šmotek, Michal; Saifutdinova, Elizaveta; Kopřivová, Jana; Bušková, Jitka; Mander, Bryce Anthony; Brunovský, Martin; Zach, Peter; Korčák, Jakub; Andrashko, Veronika; Viktorinová, Michaela; et al. (Frontiers in Pharmacology, 2020)
Serotonergic agonist psilocybin is a psychedelic with antidepressant potential. Sleep may interact with psilocybin’s antidepressant properties like other antidepressant drugs via induction of neuroplasticity. The main aim of the study was to evaluate the effect of psilocybin on sleep architecture on the night after psilocybin administration. Regarding the potential antidepressant properties, we hypothesized that psilocybin, similar to other classical antidepressants, would reduce REM sleep and prolong REM sleep latency. Moreover, we also hypothesized that psilocybin would promote slow-wave activity (SWA) expression in the first sleep cycle, a marker of sleep-related neuroplasticity. Twenty healthy volunteers (10 women, age 28-53) underwent two drug administration sessions, psilocybin or placebo, in a randomized, double-blinded design. Changes in sleep macrostructure, slow-wave activity (SWA) during the first sleep cycle, whole night EEG spectral power across frequencies in NREM and REM sleep, and changes in subjective sleep measures were analyzed. The results revealed prolonged REM sleep latency after psilocybin administration and a trend towards a decrease in overall REM sleep duration. No changes in NREM sleep were observed. Psilocybin did not affect EEG power spectra in NREM or REM sleep when examined across the whole night. However, psilocybin suppressed SWA in the first sleep cycle. No evidence was found for sleep-related neuroplasticity, however, a different dosage, timing, effect on homeostatic regulation of sleep, or other mechanisms related to antidepressant effects may play a role. Overall, this study suggests that potential antidepressant properties of psilocybin might be related to changes in sleep.